Women’s status within the household as a determinant of maternal health care use in Nigeria (2015)
Background: Although gender inequality is often cited as a barrier to improving maternal health in sub-saharan Africa, there is lack of empirical data on how women’s socio-cultural characteristics may influence use of health services in Nigeria. Objective: To describe how women’s position in the household affects receipt of maternity care services. Methods: Secondary data analysis of 10,052 and 4,590 currently married women aged 15 to 49 years from the 2008 Nigerian DHS who receive skilled antenatal and delivery care at least till pregnancy was done. Results: Receipt of skilled delivery care was by 37.9% while, natal care was by 98.4%. Education, residence and wealth index all significantly influenced receipt of maternal health care. Women who were involved in decision making on their own health (aOR=1.97; 95%CI=1.88-2.06) and were employed throughout the year (aOR=1.11; 95%CI=1.01-1.23) were more likely to receive skilled antenatal care, while those who justified physical intimate partner violence were less likely to receive both skilled antenatal care (aOR=0.92; 95%CI=0.85-0.98) and delivery services (aOR 0.54; 95% CI 0.33-0.87). Conclusion: Interventions aimed at improving maternal care should promote women empowerment (decision making, self worth, educational and economic) and should involve partners